1989
DOI: 10.1002/1097-0142(19890515)63:10<1994::aid-cncr2820631021>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A case of bronchogenic cyst with high production of antigen CA 19–9

Abstract: A 35-year-old man was hospitalized with complaints of retrosternal pain and high fever. A chest radiograph showed a large round mass in the mediastinum. Of the several tumor markers in the serum tested, only CA 19-9 was elevated. Thoracotomy revealed a cystic mass with purulent hemorrhagic materials. Histologically the cyst was lined by bronchial epithelium with no evidence of malignancy. The high level of CA 19-9 in the cystic fluid, and positive immunohistochemical staining of the bronchial glands in the cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…However, the relation between of CA19-9and bronchogenic cyst has been previously reported in only a few cases (8)(9)(10)(11)(12)(13)). …”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the relation between of CA19-9and bronchogenic cyst has been previously reported in only a few cases (8)(9)(10)(11)(12)(13)). …”
Section: Introductionsupporting
confidence: 90%
“…A small amount of to be elevated to more than 100 U/ml in benign digestive tract diseases such as chronic pancreatitis or cholelithiasis (18). Okuboet al first reported a case ofbronchogenic cyst with high level ofCA19-9 inboth serum and cystic fluidin 1989 (8). Since then there have been five reports that indicate the relationship between bronchogenic cysts and increase of the CA19-9 level in the serum or the cyst fluid (9-13).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was supported by the finding that the serum level of CA 19-9 returned to within the normal range after her total thyroidectomy (Table 2). Similar CA 19-9-producing lung cysts have been reported by Okubo et al (Okubo et al, 1989). Routinely this tumor would have been broadly defined as a follicular or papillary carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…As bronchogenic cysts are derived from the foregut, it is likely that the epithelial cells of the bronchial glands located in the wall of the cyst secreted CA 19‐9, and without clearance by the bronchial mucus into normal bronchial spaces, it resulted in a gradual accumulation of CA 19‐9 in the cyst. Although bronchogenic cysts are uncommonly associated with a raised CA 19‐9 level, there were several case reports to show that bronchogenic cysts can present similarly with an elevated serum and cystic fluid CA 19‐9 2 . All these reported cases were intrathoracic or of non‐gastric origins.…”
mentioning
confidence: 99%
“…Although bronchogenic cysts are uncommonly associated with a raised CA 19-9 level, there were several case reports to show that bronchogenic cysts can present similarly with an elevated serum and cystic fluid CA 19-9. 2 All these reported cases were intrathoracic or of non-gastric origins. Ours is perhaps the first gastric bronchogenic cyst to present as such.…”
mentioning
confidence: 99%